2018
DOI: 10.1109/tcomm.2018.2850814
|View full text |Cite
|
Sign up to set email alerts
|

3-D Polarized Modulation: System Analysis and Performance

Abstract: In this paper we present a novel modulation technique for dual polarization communication systems, which reduces the error rate compared with the existent schemes. This modulation places the symbols in a 3D constellation, rather than the classic approach of 2D. Adjusting the phase of these symbols depending on the information bits, we are able to increase the bit rate. Hence, the proposed scheme conveys information by selecting both polarization state and the phase of radiated electromagnetic wave. We also ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…According to (28), the power of ICI tends asymptotically to 0, lim/M⟶∞ E S ICI 2 = 0. Using (32), (33), and Proposition 3, we can see that the power of the new additive noise is lim/M⟶∞ E UW D,0 ′ 2 = 2/ 1 + x 2 σ 2 w , where σ 2 w denotes the power of the AWGN before ZF detection.…”
Section: 2mentioning
confidence: 99%
See 3 more Smart Citations
“…According to (28), the power of ICI tends asymptotically to 0, lim/M⟶∞ E S ICI 2 = 0. Using (32), (33), and Proposition 3, we can see that the power of the new additive noise is lim/M⟶∞ E UW D,0 ′ 2 = 2/ 1 + x 2 σ 2 w , where σ 2 w denotes the power of the AWGN before ZF detection.…”
Section: 2mentioning
confidence: 99%
“…In wireless communication, the polarization modulation (PM) is a novel modulation technique to improve the performance, such as BER [28] and energy efficiency [29][30][31][32]. Moreover, it has been found in [33] that the polarization state (PS) of the signal is insensitive to phase noise.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance of SM systems are validated via practical measurements [14], [15]. Furthermore, the SM scheme has been generalized by combining other concepts, such as the space shift keying (SSK) [16]- [20], the generalized SM (GSM) [3], the polarization shift keying system [24], [25] and the quadrature spatial modulation (QSM) [21]- [23]. In conclusion, recent studies have demonstrated that SM can be a promising wireless communication technique.…”
Section: Introductionmentioning
confidence: 99%